From managing information to managing relationships: Reframing the role of ICT - Galbreath, Jeremy (Curtin University of Technology, 2007)
Today, one could argue that business is in a relationship age rather than an information age. In a relationship age economy, competitive success largely depends on managing the complex interdependencies of the firm?s relationship assets. Indeed, the firm?s relationship assets?its customer assets, employee assets, partner assets and supplier assets?lie at the heart of a firm?s ability to create value. To more effectively manage relationship assets, firms should strategically apply ICT within a framework that allows them to assess, monitor and measure such assets. In this article, one such framework is proposed. Important ICT that are necessary for the effective management of relationship assets are also described.